Eksekusi Putusan Arbitrase Internasional Dalam Sistem Hukum Indonesia - Tutojo Tutojo (Jurnal Penelitian Hukum Legalitas, 2015)
International arbitration decision shall be in accordance with the provisions of laws and regulations or legal system in the country. The legal system has three elements, namely the substance of the law, the legal structure and legal culture. Study of this law is the study of normative law, and based on the legal theory of Friedman, the legal review was conducted by a study from the point of legal substance, namely legislation, including its principles, judicial authorities, procedural law, and of legal culture. Qualitative analysis method was used to examine if execution of International Arbitration Decision is appropriate with Indonesian Law System. Based on the study of the law, that the execution of International Arbitral Awards in London on July 3rd 2006 on Transportation Contract Dispute Through the Sea in compliance with Indonesian Law System. International Arbitration Decision Execution is hampered because of the lack of good faith of the defendant, the defendant does not voluntarily execute commands authorized Courts.